Pervaporation Membrane Containing Electrospun Poly(Vinyl Alcohol) Composite Nanofibre Layer For Dehydration Of 1,4-Dioxane - Wen, Yeang Qian (2018)
In this study, novel asymmetric membranes with pre-selective layer consist of electrospun poly(vinyl alcohol) (PVA) nanofibres and electrospun PVA nanofibres integrated with two different types of hydrophilic fillers i.e. micron-sized copper benzene-1,3,5-tricarboxylate (Cu-BTC) and nano-sized carboxyl multi-walled carbon nanotube (COOH-MWCNT), respectively were successfully fabricated. Electrospun PVA nanofibres, Cu-BTC/PVA and COOH-MWCNT/PVA composite nanofibres were deposited on dense PVA membranes to form M0, MCuBTC and MCOOH-MWCNT asymmetric membranes, respectively. All asymmetric membranes showed improved performance in the pervaporation dehydration of aqueous 1,4-dioxane solutions. This phenomenon is due to the electrospun hydrophilic nanofibre layer serving as a hydrophilic pre-selective barrier that traps water molecules. The pervaporation separation performance increased in the following order: dense PVA membrane < M0 < MCOOH-MWCNT < MCuBTC. Compared to dense PVA membrane, M0 exhibited an increment of almost 50% in water permeation flux accompanied with an increase in separation factor. Between MCuBTC and MCOOH-MWCNT membranes, MCuBTC membranes exhibited better separation performance. The performance of the MCuBTC membranes increases with increasing Cu-BTC loading of 0.5 to 1.0 wt.%. Among all the membranes studied, MCuBTC membrane incorporated with 1.0 wt.% Cu-BTC (MCuBTC(1.0)) exhibited the highest permeation flux and separation factor with a total permeation flux of 87.69 g/m2·h, separation factor of up to 1852.32, water permeance of 2176.20 GPU, and water selectivity of 1417.52. The water permeation flux of the MCuBTC(1.0) membrane was double of that of the dense PVA membrane, while the separation factor increased from 392.65 to 1852.32. When compared to M0, MCuBTC(1.0) membrane provided an enhancement of nearly 40% in water permeation flux along with an increase in separation factor. However, among the MCOOH-MWCNT membranes integrated with 0.5 and 1.0 wt.% COOH-MWCNT, i.e. MCOOH-MWCNT(0.5) and MCOOH-MWCNT(1.0), respectively, better separation performance was demonstrated by MCOOH-MWCNT(0.5) with a total permeation flux of 75.71 g/m2·h, separation factor of 605.35, water permeance of 1836.08 GPU and membrane selectivity of 462.30 for water. An increment of around 80% and 20% in water permeation flux was achieved by the MCOOH-MWCNT(0.5) when compared to that of the dense PVA membrane and M0, respectively. Although the separation factor of MCOOH-MWCNT(0.5) increased from 392.65 to 605.35 when compared to the dense PVA membrane, a slight decrease in separation factor from 682.11 to 605.35 was observed when compared to M0. The parameters estimated using Rautenbach model showed that the dehydration of aqueous 1,4-dioxane solutions via pervaporation is dominantly governed by sorption process.